Hotel Interdepartmental Communication: A Case of F&B Service and Sales & Marketing at Mercure Bandung Nexa - Musadad, Musadad; Dianita, Indria Angga; Dirgantara, Pradipta (Institut Pariwisata Trisakti, 2021)
This study sought to investigate the communication between the Food & Beverage Department and the Sales & Marketing Department at Mercure Bandung Nexa through the perspective of hotel interdepartmental communication. It was benefited from employing a qualitative method. The data collection was conducted through in-depth interviews with the managers of the two departments and field observations. The data collected was then analyzed and carried out through the elements of communication: people (sender and receiver), message, channel, noise, feedback, and effect. This study found that communication between the two departments goes well to keep the service excellent. Based on the analysis of the elements of communication, the only major obstacle is the sudden event that can disrupt the communication process. This result has brought discussion in the context of excellent service being delivered through the communication between the Food & Beverage Department and Sales & Marketing Department. However, this study is limited in the number of informants. More informants should be involved to gather more reliable and deeper data. After all, this study contributes to enriching the application of Interdepartmental Communication in organizations, especially in a hotel. Keywords: Interdepartmental Communication, F&B Service, Sales & Marketing